Type 2 and type 17 effector cells are increased in the duodenal mucosa but not peripheral blood of patients with functional dyspepsia - Burns, Grace L.; Bruce, Jessica K.; Minahan, Kyra; Mathe, Andrea; Fairlie, Thomas; Cameron, Raquel; Naudin, Crystal; Nair, Prema M.; Potter, Michael D. E.; Irani, Mudar Zand; Bollipo, Steven; Foster, Robert; et al. (Frontiers in Immunology, 2023)
Background: Functional dyspepsia is characterised by chronic symptoms of post-prandial distress or epigastric pain not associated with defined structural pathology. Increased peripheral gut-homing T cells have been previously identified in patients. To date, it is unknown if these T cells were antigen-experienced, or if a specific phenotype was associated with FD. Objective: This study aimed to characterise T cell populations in the blood and duodenal mucosa of FD patients that may be implicated in disease pathophysiology. Methods: We identified duodenal T cell populations from 23 controls and 49 Rome III FD patients by flow cytometry using a surface marker antibody panel. We also analysed T cell populations in peripheral blood from 37 controls and 61 patients. Where available, we examined the number of duodenal eosinophils in patients and controls. Results: There was a shift in the duodenal T helper cell balance in FD patients compared to controls. For example, patients had increased duodenal mucosal Th2 populations in the effector (13.0316.11, 19.8415.51, p=0.038), central memory (23.7518.97, 37.5217.51, p=0.007) and effector memory (9.8010.50 vs 20.5314.15, p=0.001) populations. Th17 populations were also increased in the effector (31.7424.73 vs 45.5723.75, p=0.03) and effector memory (11.958.42 vs 18.4415.63, p=0.027) subsets. Peripheral T cell populations were unchanged between FD and control. Conclusion: Our findings identify an association between lymphocyte populations and FD, specifically a Th2 and Th17 signature in the duodenal mucosa. The presence of effector and memory cells suggest that the microinflammation in FD is antigen driven.